Genetic diversity of Bartonella infection in residential and field rodents in Hebei, China - Jian, Rui; Ren, Qing; Xue, Jing; Xie, Guang-Cheng; Wang, Jiangli; Chen, Guo-Qing; Du, Luanying; Guo, Wen-Ping (Frontiers in Microbiology, 2022)
Rodents are the primary natural reservoirs of Bartonella spp., and some of which are zoonotic causative agents. Hence, surveillance of Bartonella sp. infection in rodents is very important for the prevention of human bartonellosis caused by them. In this study, rodents were captured, and their spleen samples were collected for Bartonella sp. DNA detection and identification by amplifying the 16S rRNA, gltA, and ftsz genes using semi-nested polymerase chain reaction (PCR). The results indicated that Bartonella sp. DNA was detected in seven Rattus norvegicus individuals with a detection rate of 6.7% in Chengde City and bacterial DNA in 31 Apodemus agrarius individuals with a detection rate of 28.4% in Handan City. The DNA detection rate across the genders and ages of rodents was not found to be statistically significant. Furthermore, sequence analysis of the above-mentioned three genes demonstrated that at least eight Bartonella species were circulating in Hebei Province, of which three, including Bartonella rattimassiliensis, Bartonella grahamii, and Bartonella tribocorum, are human pathogens, thus suggesting the existence of a major public health risk. Overall, these results revealed the detection rate and genetic diversity of Bartonella species infection in rodents in Hebei Province, which could be potentially helpful for the prevention of bartonellosis caused by rodent-associated Bartonella species. This study highlights the urgent need for the surveillance of Bartonella infections in rodents and ectoparasites that affect both rodents and humans and can cause fever of unknown origin or endocarditis.